Photodynamic therapy as a coadjutant in the treatment of halitosis of oral origin: narrative literature review (Research, Society and Development, 2021)
Halitosis, popularly known as bad breath, is a term used to describe unpleasant odors from the oral cavity, regardless of its cause. Current studies have approached that Antimicrobial Photodynamic Therapy (aPDT) has been used as an adjunct in the treatment of this pathology. The general objective of this study is to review the literature on the efficacy of photodynamic therapy in the treatment of oral halitosis and the specific objective is to review the literature on the action of photodynamic therapy in the treatment of oral halitosis. A narrative literature review was carried out and the survey of studies was carried out in the PubMed, Virtual Health Library and CAPES journals databases, with the descriptors “Halitosis”; “Photochemotherapy”; “Photodynamic Therapy”; “Therapeutics” and “Oral Cavity”. The articles were published between 2017 and 2021, in English, Portuguese and Spanish. After that, 24 articles were included in this review. The idea of carrying out this study first came from the large portion of the population with halitosis, which directly interferes with quality of life. aPDT is an option to reduce the amount of microorganisms present in the mouth and is based on the combination of a light source of adequate wavelength with a photosensitizer and oxygen from the environment. aPDT proved to be effective in reducing hydrogen sulfide immediately after its application, reducing oral halitosis in a short period of time.